Efektivitas Penggunaan Virtual lab Qreatif Educative terhadap Peningkatan Pemahaman Konsep Siswa SMP pada Materi Suhu dan Kalor - Lutfiah, Afi Fatul; Akhdinirwanto, Wakhid (PendIPA Journal of Science Education, 2026)
This study aims to examine the effectiveness of implementing Qreatif Educative Virtual Lab in improving middle school students' conceptual understanding of temperature and heat. This study uses a quasi-experimental approach with a single-group pretest-posttest design. The research subjects consisted of 18 students from class VII A at a junior high school in Kemiri District, Purworejo Regency, in the 2025/2026 academic year. The research instrument was a 10-item multiple-choice test administered before and after the treatment. The data were analyzed using the N-Gain test to assess the increase in conceptual understanding and the paired t-test to test the difference in learning outcomes. The average student score increased from 43.8 to 65.5 with an N-Gain value of 0.376, which falls into the moderate category. The paired t-test showed a significant difference (p < 0.05). Thus, the use of the Qreatif Educative Virtual Lab proved to be effective in improving students' conceptual understanding, although further optimization in the learning process is still needed.